2022
DOI: 10.3389/fcvm.2022.994085
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and persistence to oral anticoagulants in patients with atrial fibrillation: A Belgian nationwide cohort study

Abstract: BackgroundSince non-vitamin K antagonist oral anticoagulants (NOACs) do not require coagulation monitoring, concerns of lower adherence and persistence to NOACs than vitamin K antagonists (VKAs) have been raised. Moreover, little is known on the frequency of permanent cessation and switching between anticoagulants in patients with atrial fibrillation (AF). Therefore, persistence, reinitiation, switching and adherence to oral anticoagulants (OACs) were investigated.Materials and methodsAF patients with a first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Data were provided by two nationwide databases, the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD), as described before ( Grymonprez et al, 2022 ). The IMA centralizes all claims data from Belgian health insurance funds on reimbursed ambulatory and hospital care, including demographic characteristics (age, sex, date of death), medical procedures (diagnostic or therapeutic procedures and other reimbursed care) and drug prescription claims ( Grymonprez et al, 2022 ; IMA/AIM, 2021 ). As health insurance is legally mandatory in Belgium, the source population represents all legal residents with reimbursed medication or care.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data were provided by two nationwide databases, the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD), as described before ( Grymonprez et al, 2022 ). The IMA centralizes all claims data from Belgian health insurance funds on reimbursed ambulatory and hospital care, including demographic characteristics (age, sex, date of death), medical procedures (diagnostic or therapeutic procedures and other reimbursed care) and drug prescription claims ( Grymonprez et al, 2022 ; IMA/AIM, 2021 ). As health insurance is legally mandatory in Belgium, the source population represents all legal residents with reimbursed medication or care.…”
Section: Methodsmentioning
confidence: 99%
“…As health insurance is legally mandatory in Belgium, the source population represents all legal residents with reimbursed medication or care. The MHD aggregates hospital discharge diagnoses of every hospital admission in Belgium, coded in International Classification of Diseases (ICD) codes (ICD-9 up to 2014, ICD-10 from 2015 onwards) ( MZG, 2021 ; Grymonprez et al, 2022 ). This study was approved by the IMA and MHD database administrators as well as by the ‘Sectoral Committee of Social Security and Health, Section Health’, a subcommittee of the Belgian Commission for the Protection of Privacy (approval code IVC/KSZG/20/344) ( eHealth-platform, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MHD, collected by the Belgian Ministry of Health, aggregates hospital discharge diagnoses of every admission in Belgian hospitals (including hospitalizations, daycare stays and emergency room contacts), coded in International Classification of Diseases (ICD) codes (ICD-9 up to 2014, ICD-10 from 2015 onwards). 13,15,16 All single cases of the study population could be identified in both databases. The trusted third party 'eHealth' was responsible for deterministically linking both databases using the national social security number as unique patient identifier.…”
Section: Source Populationmentioning
confidence: 99%